2014
DOI: 10.1021/jp501622d
|View full text |Cite
|
Sign up to set email alerts
|

How To Tackle the Issues in Free Energy Simulations of Long Amphiphiles Interacting with Lipid Membranes: Convergence and Local Membrane Deformations

Abstract: One of the great challenges in membrane biophysics is to find a means to foster the transport of drugs across complex membrane structures. In this spirit, we elucidate methodological challenges associated with free energy computations of complex chainlike molecules across lipid membranes. As an appropriate standard molecule to this end, we consider 7-nitrobenz-2-oxa-1,3-diazol-4-yl-labeled fatty amine, NBD-Cn, which is here dealt with as a homologous series with varying chain lengths. We found the membrane-wat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
103
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(107 citation statements)
references
References 57 publications
4
103
0
Order By: Relevance
“…This effect has been found in previous studies, and has been attributed primarily to the presence of more than one slow variable characterizing membrane permeation, among which peptide orientation and large-scale membrane structural fluctuations have been proposed. 25,27,30,96 The accommodation of additional slow variables is an exciting topic of current inquiry.…”
Section: Discussionmentioning
confidence: 99%
“…This effect has been found in previous studies, and has been attributed primarily to the presence of more than one slow variable characterizing membrane permeation, among which peptide orientation and large-scale membrane structural fluctuations have been proposed. 25,27,30,96 The accommodation of additional slow variables is an exciting topic of current inquiry.…”
Section: Discussionmentioning
confidence: 99%
“…This probe in particular displays perfect matching with POPC acyl chains, and its packing and ordering abilities may be related to the reported favourable partition into liquid ordered phases of NBD-diC 16 PE and NBD-diC 18 PE (the latter should be better accommodated inside domains enriched in longer, predominantly saturated chains such as those of sphingomyelin inside lipid rafts). However, full clarification of this matter will involve additional work, focused on cholesterol-containing liquid ordered bilayers, and including calculation of the changes in solute free energy across the bilayer (as recently done by us for the NBD-C n series in POPC 89 ).…”
Section: Discussionmentioning
confidence: 99%
“…30 for discussion about translocation of long amphiphilic chains moving through a membrane, a system with many similarities to ours). Specifically, in our study we found that the lipid bilayer was too easily deformed while pushing the peptide inside of it, in some cases to the point of reaching the boundary of the simulation box, such that it could affect the assumptions of periodic boundary conditions (PBC) (one imagines a smooth transition from one periodic cell to the other, not transitions where the membrane forms sharp angles).…”
Section: B Umbrella Samplingmentioning
confidence: 93%